Coupled quintessence - Amendola, Luca (Physical review. D, Particles, fields, gravitation, and cosmology, 2000)
A new component of the cosmic medium, a light scalar field or “quintessence,” has been proposed recently to explain cosmic acceleration with a dynamical cosmological constant. Such a field is expected to be coupled explicitly to ordinary matter, unless some unknown symmetry prevents it. I investigate the cosmological consequences of a coupled quintessence (CQ) model, assuming an exponential potential and a linear coupling. This model is conformally equivalent to Brans-Dicke Lagrangians with any power-law potential. I evaluate the density perturbations on the cosmic microwave background and on the galaxy distribution at the present and derive bounds on the coupling constant from the comparison with observational data. A novel feature of CQ is that during the matter dominated era the scalar field has a finite and almost constant energy density. This epoch, denoted as φMDE, is a saddle point in the dynamical phase space. The φMDE is responsible of several differences with respect to uncoupled quintessence: the multipole spectrum of the microwave background is tilted at large angles, the acoustic peaks are shifted, their amplitude is changed, and the present 8 Mpc/h density variance is diminished. The present data constrain the dimensionless coupling constant to |β|<~0.1 assuming Ωm=0.3 and a primordial fluctuation slope ns=1.